"This Is a World of Spectacles": Cyclical Narratives and Circular Visionary Formations in Elif Shafak's The Gaze. Issue 3 (27th May 2017) - Atayurt-Fenge, Zeynep Z.
ABSTRACT: Published in 2000, the contemporary Turkish writer Elif Shafak's The Gaze explores notions of looking and being looked at within a polyphonic circular narrative, made manifest through Shafak's juxtaposition of various stories. With contemporary Istanbul at its center, the novel fluctuates between three subnarratives set in nineteenth-century Istanbul, seventeenth-century Siberia, and nineteenth-century France, all of which culminate in a circular carnivalesque whole. Within the frame of a critical exploration of the textual subtleties of the novel, this essay seeks to examine the ways in which the formal circular constructions employed in the novel offer a stylistically stimulating space to engage with the social and cultural implications of seeing and being seen. Through an exploration of multifarious meanings encompassing the concept of the gaze, this essay will examine the discursive functions of the circular form in Shafak's work in the light of various folkloric and literary contexts.